2020
DOI: 10.2147/rmhp.s258186
|View full text |Cite
|
Sign up to set email alerts
|

<p>Longer Delays in Diagnosis and Treatment of Pulmonary Tuberculosis in Pastoralist Setting, Eastern Ethiopia</p>

Abstract: This study aimed to assess the extent of patient, health system and total delays in diagnosis and treatment of pulmonary tuberculosis (TB) in Somali pastoralist setting, Ethiopia. Patients and Methods: A cross-sectional study among 444 confirmed new pulmonary TB patients aged ≥15 years in 5 TB care units was conducted between December 2017 and October 2018. Data were collected using a structured questionnaire and record review. We measured delays from symptom onset to provider visit, provider visit to diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…The median patients’ delay of our current study was longer when compared with studies done in Ethiopia, at a national level that reported 21 days, [ 5 ] 17 days at Addis Ababa, [ 18 ] and 25 days in southwestern Ethiopia [ 24 ] but comparable with studies in the country that reported a median of patients’ delay 30 days at Adama, central Ethiopia, [ 28 ] at Gamo zone, south Ethiopia, [ 29 ] and Somali region, eastern Ethiopia. [ 30 ] The difference might be due to the accessibility to health facilities, socioeconomic factors, and study populations. Besides, the patients’ delay was longer among rural residents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median patients’ delay of our current study was longer when compared with studies done in Ethiopia, at a national level that reported 21 days, [ 5 ] 17 days at Addis Ababa, [ 18 ] and 25 days in southwestern Ethiopia [ 24 ] but comparable with studies in the country that reported a median of patients’ delay 30 days at Adama, central Ethiopia, [ 28 ] at Gamo zone, south Ethiopia, [ 29 ] and Somali region, eastern Ethiopia. [ 30 ] The difference might be due to the accessibility to health facilities, socioeconomic factors, and study populations. Besides, the patients’ delay was longer among rural residents.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the costs of transportation, accommodation, and others such as child care at home. [ 28 , 30 ] Patients’ delay was low among ART patients. This could be due to the existing integrated program to control the TB/HIV co-infection that initiated the screening and diagnosis at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…4 Early diagnoses and treatment are key elements of successful TB control; however, a major challenge of TB control and prevention programs is a delay in seeking health care. 5,6…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the individual and community related factors that lead to delayed TB diagnosis and treatment is essential to evaluate the effectiveness of TB control programs to develop interventions to reduce TB transmission in communities. 6 Furthermore, understanding the health-seeking behavior of patients with symptoms suggestive of TB is important to design national responses to improve TB services in health facilities. 1…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation